2016
DOI: 10.4102/phcfm.v8i2.996
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to men’s reluctance to seek HIV counselling and testing at Primary Health Care facilities in Vhembe District of South Africa

Abstract: BackgroundVoluntary HIV antibody Counselling and Testing (HCT) is a cornerstone of HIV prevention in South Africa because it has the potential to prevent HIV transmission. The government of South Africa has for a long time been investing heavily in fighting the spread of HIV and/or AIDS. However, men rarely utilise this service.AimThe aim of this study was to explore the factors contributing to the reluctance of men to seek HCT in the primary health facilities in Vhembe District.SettingThe study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
30
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 8 publications
5
30
0
2
Order By: Relevance
“…HIV testing norms also appeared to be an especially influential correlate of men's testing behavior, with low perceived social support for testing posing a major obstacle [31,32]. Qualitative research suggests that for men, the prospect of receiving an HIV diagnosis is associated with fears of discrimination and loss of material resources through lost employment, rejection from family and community, and threats to masculinity [24,59]. Women also anticipated stigma reactions from their partners in response to an HIV diagnosis; with some women reluctant to test or ask partners to test due to concerns that their partners may force them to leave their home based on the test results [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV testing norms also appeared to be an especially influential correlate of men's testing behavior, with low perceived social support for testing posing a major obstacle [31,32]. Qualitative research suggests that for men, the prospect of receiving an HIV diagnosis is associated with fears of discrimination and loss of material resources through lost employment, rejection from family and community, and threats to masculinity [24,59]. Women also anticipated stigma reactions from their partners in response to an HIV diagnosis; with some women reluctant to test or ask partners to test due to concerns that their partners may force them to leave their home based on the test results [37].…”
Section: Discussionmentioning
confidence: 99%
“…Perceived stigma and discrimination were found to vary across study populations, with higher rates of stigma and overt discrimination occurring in socioeconomically disadvantaged urban and rural communities relative to betterresourced settings [19][20][21][22]. With respect to HIV testing, women tended to report more frequent testing than men, with men often indicating hesitation to attend primary health clinics due to concern that they may be perceived as less masculine [23,24]. Two large quantitative surveys, however, reported conflicted findings with regard to gender, stigma and HIV testing.…”
Section: South Africamentioning
confidence: 99%
“…Study participants reported that men seemed fearful of HIV and ART and would refuse to be tested. The fear of receiving a HIV test is well documented in the literature, with previous studies highlighting fears of loss of masculinity, power, and pride with an HIV-positive test result [ 11 , 17 ]. Participants reported that even when their male partner was very ill they would still refuse to attend the facility to receive a HIV test or start treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Results from this study show that many of the earlier truths about HIV and ART continue to persist. Old ideas of HIV as a death sentence continue to linger and beliefs such as these continue to discourage men from successfully engaging in HIV testing and treatment [ 11 , 38 ]. Fear of visible side effects from the earlier drug regimens (primarily stavudine) were documented in this study and have been seen in other literature [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Independente do sexo ou nacionalidade, o temor do resultado do teste é uma constante no relato dos usuários, bem como a relação profissional-usuário. Em pesquisa realizada com homens na África do Sul, foram expressos sentimentos de medo por conhecerem seu status, a maioria falou que não tinha confiança no comportamento dos profissionais 30. Com isso, evidencia-se o estigma relacionado ao HIV/Aids como forte influência tanto nos profissionais, como nos usuários.…”
unclassified